Les défis de l’assurance I.A.R.D - Dussault, Claude (Assurances)

(untitled) (HEC Montréal, 1987)
In his article on the challenges of the property and casualty insurance industry, Mr. Claude Dussault exposes both the difficulties that lie ahead and the solutions. We are certain that the following text will prove most interesting.